La science-fiction fantastique de Maurice Renard - Arthur B. Evans (ReS Futurae)
Although one of the most prominent writers (and theorists) of science fiction in throughout the period of 1900-1930, Maurice Renard has heretofore received very little critical attention outside his native land. His neglect among Anglo-American literary scholars is most likely the result of two factors : first, very few English translations of Renard's works exist (and those that do are of inferior quality) and, second, the basic nature of Renard's sf tends to challenge our more modern notions of genre specificity when defining the sf canon-i.e., his stories appear to continually cross the line into Gothic horror, mythological fantasy, and detective mysteries. This article presents a brief synopsis of Maurice Renard's life and literary ideas (e.g., the "scientific- marvellous"), and offers a detailed discussion of Renard's many novels and short stories, which, often resembling a kind of cross-hybridization between Wells and Poe, can together perhaps best be labelled "fantastic sf."